(untitled) (Advancements in Homeopathic Research, 2025)
A Cross Sectional Survey of Kofeez Cough Syrup in Clinical Practice Introduction: Cough is one of the most frequently reported medical symptoms in clinical practice. Its features, duration and severity depend on the etiology. The symptoms are greatly affected by environmental factors also. Kofeez Cough Syrup, a homoeopathic formulation by Medisynth, is widely prescribed for all types of coughs across age groups since decades. The present survey is aimed to assess doctor’s perception, prescription pattern, and clinical experience with Kofeez Cough Syrup across India.